The Use of Concept Maps in the Process of Independent Study of Educational Material in Higher Mathematics - Norik, Larisa; Lebedeva, Irina (Educational Challenges, 2021)
The purpose of the article is to analyze the impact of concept mapping on the level and quality of assimilation of learning material in higher mathematics in the process of independent study. Methodology. Based on a review of the main provisions of modern theory of learning and generalization of research results presented in scientific papers on the scope of application of concept maps in the learning process, such a training experiment was conducted. For students of the two experimental groups on a certain topic of the discipline “Higher Mathematics” were offered to build conceptual maps in addition to the common teaching methods. It considered as an independent creative task. In the other two groups, which were under control, students had to study the same topic of the discipline, using traditional methods. Results. It was determined that the results of the colloquium composed of students of experimental groups were significantly higher than those of students of control groups who did not use mapping as a method of learning during independent work. The average score obtained by students of experimental groups for the colloquium was almost 80 points, while for students of control groups it was only 72 points. Using Student’s test, the significance of the difference between the values of the sample averages of these indicators proved. If we compare the average scores for different types of tasks, the most significant was the difference in the performance of heuristic tasks, which reflect the ability to apply the acquired knowledge to solve practical problems of economic content. Conclusions. The positive influence of the use of concept mapping in independent work of students established, which proves the thesis about the feasibility of using concept mapping as a learning tool. Further introduction of concept maps in the educational process should be based on the development of complex theoretical and practical, as well as competency-oriented tasks.